Potential Abuse On The Issuance Of Online Medical Certificates By Doctors: A Criminological Review - Supardi Hamid; Teddy Rusmawan (Faculty of Law, Universitas Jenderal Soedirman, 2023)
The right to health for all Indonesian people is guaranteed in Article 28H of the 1945 Constitution. Doctors and dentists are the main professions in the field of health, as stated in Law No. 29 of 2004 concerning Medical Practice. After the Covid 19 Pandemic ended, there has been a significant shift, with the rise of health services through digital and application media, ease of access to health, and online sick notes. This facility can be misused for work purposes etc. Moreover, a defendant can avoid the investigation process by easily obtaining a sick note online; this service cannot optimize patient examinations because it's not done face-to-face. Therefore it is important to examine the making of online sick notes, which have the potential to become a form of crime and be reviewed from the perspective of a criminological approach. This study aims to examine online sick notes as a crime and whether this activity is by Law No. 29 of 2004 reviewed in criminology. The research method used is normative legal research with statutory and conceptual approaches. The results of this study conclude that making sick notes online is not by Law No. 29 of 2004 and violates Article 7 KODEKI so that it can be considered a form of crime. In contrast, from a criminological point of view, through communication and convenience, this makes the perpetrator according to the science of criminology as contained in the differential theory association.Keywords: Criminology, Medical Practice, Online Sick Letter